Analisis Strategi Bisnis PT Astra Agro Lestari Tbk dengan Pendekatan SWOT, SPACE, BCG, IE Matrix, dan Grand Strategy Matrix - Natalisa Margaretha (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to formulate an effective business strategy for PT Astra Agro Lestari Tbk in addressing the increasingly competitive dynamics of the palm oil industry, along with the growing demand for sustainability practices. The study employs a comprehensive strategic management approach through three main stages: the input stage (EFE, IFE, CPM), the matching stage (SWOT, SPACE, BCG, IE, and Grand Strategy Matrix), and the decision stage (QSPM). The analysis results indicate that the company holds a relatively strong strategic position, with an EFE score of 2.96 and an IFE score of 2.89, and demonstrates a competitive advantage over its rivals. In the matching stage, the company is positioned in the aggressive quadrant and falls under the “Stars” category, reflecting high growth potential. Based on the QSPM analysis, the recommended priority strategy is product development, with a Total Attractive Score (TAS) of 6.56, which is considered superior to the market penetration strategy. This strategy focuses on downstream product diversification to enhance value-added and reduce dependence on CPO commodities. The implementation of this strategy is expected to strengthen the company’s competitiveness, improve long-term performance, and support business sustainability within the palm oil industry